Peran Orang tua dalam Pembentukan Norma Kesopanan Anak di Stasi Santa Perawan Maria Ratu Kamangta - Singal, Fecky Evendy; Lapong, Glen Rafael (Sekolah Tinggi Pastoral Don Bosco Tomohon, 2024)
This study aims to describe the role of parents in the formation of children's politeness norms, factors that support and inhibit the role of parents in the formation of children's politeness norms, and efforts made by parents in the formation of children's politeness norms at Santa Perawan Maria Ratu Kamangta Station. This study uses a qualitative approach to obtain more in-depth data on the role of parents in the formation of children's politeness norms at Santa Perawan Maria Ratu Kamangta Station. The results of the study indicate that the Role of Parents in the Formation of Children's Politeness Norms at Santa Perawan Maria Ratu Kamangta Station is carried out by supervising every behavior shown by children and teaching children to be individuals who are always grateful for the help of others. There are also factors that support the role of parents in the formation of children's politeness norms, namely the child's attitude of being open to advice given by parents and good communication between children and parents. The inhibiting factors are the negative influence of the surrounding environment and the lack of time for parents to supervise children's activities. For this reason, efforts that parents must make in the formation of children's politeness norms are educating children to be individuals who can accept direction and reprimands from others, fostering politeness in children, and limiting children from being involved in relationships that have a bad influence.